Grafomotorické dovednosti Nové přístupy k diagnostice - Šafárová, Katarína (Masaryk University Press, 2022)
Title in English: Graphomotor skills: New approaches to the diagnosis This book focuses on graphomotor skills, their disorders and brings new possibilities to their diagnosis. The introduction discusses various theories of writing and the development of graphomotor skills and writing. It also defines graphomotor disorders and developmental dysgraphia and offers an overview of diagnostic methods for assessing handwriting disabilities. In the final chapter, the authors present an original approach to diagnosing graphomotor disabilities based on an objective analysis of online handwriting. The resulting "Graphomotor and Handwriting Disabilities Rating Scale" (GHDRS) allows for a detailed assessment of the sources of a child's difficulties. The book is intended primarily for workers in the school guidance system, especially special educators and psychologists, but also for others interested in graphomotor skills.